Comparison of external load measures per minute based on match seasonal periods and playing positions of a soccer Turkish super league team - Akyildiz, Zeki; Yuksel, Yilmaz; Birgonul, Yasar; Ceylan, Halil Ibrahim; Oliveira, Rafael; Cene, Erhan; Parim, Coskun; Clemente, Filipe Manuel; Nobari, Hadi (BMC, 2023)
BackgroundTurkish Super League teams need more information about the external load. Considering the specific country and the coaches' philosophies, the purpose of this study was to compare the external match load of a Turkish Super League team considering the different playing positions and in-season periods.MethodologyA longitudinal study design was employed by observing 29 official matches of the same team. A total of fifteen players, consisting of five defenders, five midfielders, and five forwards, were analyzed using the Sentio Sports Optical Tracking System. The following outcomes were extracted in each match: total distance (TD), walking [from 0 to 7.2 km/h], jogging [from 7.2 to 14.4 km/h], running [from 14.4 to 20 km/h], high speed running (HSR) [> 20 km/h], metabolic power (MP), maximum deceleration (Dec(max)) [Dec 3 m/s(2)], and total acceleration distance (Acc(total)). Statistical analysis consisted of ANOVA and Bonferroni correction post hoc tests.ResultsThe main results showed that all variables were similar between periods of the season (p > 0.05) except for walking (p = 0.021 witha large effect size), which revealed lower values in the mid-season period. When analyzing periods of the season considering playing positions, there were several significant results for TD, walking, jogging, running, HSR, Dec(total) and Acc(total) (p < 0.05, with small to large effects). A tendency for higher values was noted in the mid and end-season. Considering the playing positions comparisons, midfielders showed higher values than defenders for TD, MP, Dec(total) and Acc(total) (p < 0.05 with large effect for all). Midfielders also showed higher values than forwards for TD, jogging, Dec(total) and Acc(total) (p < 0.05 with a large effect for all).ConclusionsThe present study emphasizes the significance of analyzing data based on minute, playing position, and season period. Findings reveal that defenders consistently displayed the lowest values in all external load measures during matches compared to other positions throughout the season. Furthermore, midfielders demonstrated a higher activity profile during the initial and middle stages of the season compared to other positions, with a slight tendency to decrease load towards the end of the season.
Keywords: Match Analysis; External load; Playing positions; Seasonal periods; Soccer; METABOLIC POWER; ELITE SOCCER; PERFORMANCE; PLAYERS; Orthopedics; Rheumatology